2023
DOI: 10.1186/s12954-023-00736-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in opioid overdose prevention: comparison of the naloxone care cascade in White, Latinx, and Black people who use opioids in New York City

Abstract: Background Drug overdose mortality is rising precipitously among Black people who use drugs. In NYC, the overdose mortality rate is now highest in Black (38.2 per 100,000) followed by the Latinx (33.6 per 100,000) and white (32.7 per 100,000) residents. Improved understanding of access to harm reduction including naloxone across racial/ethnic groups is warranted. Methods Using data from an ongoing study of people who use illicit opioids in NYC (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…While many harm reduction practices originate from racially and ethnically minoritized communities, our findings echo prior studies [33][34][35] that revealed less access to harm reduction among Black, Latine, and LEP patients, and those primarily using stimulants. This is notable given structural racism's role in the disproportionate criminalization of Black and Latine people who use drugs, racial and languagebased health care disparities (including access to SUD treatment), and disproportionate overdose deaths among Black and Indigenous communities.…”
Section: Discussionsupporting
confidence: 85%
“…While many harm reduction practices originate from racially and ethnically minoritized communities, our findings echo prior studies [33][34][35] that revealed less access to harm reduction among Black, Latine, and LEP patients, and those primarily using stimulants. This is notable given structural racism's role in the disproportionate criminalization of Black and Latine people who use drugs, racial and languagebased health care disparities (including access to SUD treatment), and disproportionate overdose deaths among Black and Indigenous communities.…”
Section: Discussionsupporting
confidence: 85%
“…20 A recently published study evaluating factors associated with naloxone access by race and ethnicity in New York City also discovered gaps in naloxone training and possession, and found Black participants were less likely than White participants to be trained in naloxone administration and currently have naloxone. 21 All the aforementioned results align with the finding from the present work, where the highest frequency of naloxone possession was among non-Hispanic White participants who use opioids, and the group with the lowest reported utilization of harm reduction measures and naloxone possession were non-Hispanic Black participants. This may be rooted in the common misconception among individuals who do not use opioids that they are immune from opioid exposure and do not need to carry naloxone.…”
Section: E91supporting
confidence: 90%
“…Our findings were consistent with the results of a prior study that evaluated engagement in overdose prevention among PWID, and showed that Hispanic and non-Hispanic Black PWID were less likely than non-Hispanic White PWID to have received overdose prevention training and have used or received naloxone 20. A recently published study evaluating factors associated with naloxone access by race and ethnicity in New York City also discovered gaps in naloxone training and possession, and found Black participants were less likely than White participants to be trained in naloxone administration and currently have naloxone 21. All the aforementioned results align with the finding from the present work, where the highest frequency of naloxone possession was among non-Hispanic White participants who use opioids, and the group with the lowest reported utilization of harm reduction measures and naloxone possession were non-Hispanic Black participants.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 For example, minoritized individuals have disparities in naloxone training, possession, and use compared with White individuals. 28 Moreover, only 5% of individuals with an opioid use disorder have access to methadone. 29 This treatment gap is largely attributed to complex intersections of determinants of health and geographical region, with a dearth of office-based buprenorphine availability for Black individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a differential availability of treatment services based on social determinants of health that can directly affect marginalized populations such as women and those who identify as Black or Indigenous 26,27 . For example, minoritized individuals have disparities in naloxone training, possession, and use compared with White individuals 28 . Moreover, only 5% of individuals with an opioid use disorder have access to methadone 29 .…”
Section: Discussionmentioning
confidence: 99%